Paula Meehan’s "Cell": The Imprisoned Dialogue of Female Discourses - Poloczek, Katarzyna (Research in Language, 2014)
The paper discusses Paula Mehan’s play Cell with focus on the female discourses present in the context of this literary work and the multifold metaphorisation that both the title of the work and the contents invite. The discourses are analysed against the relevant social background and critical literature. The focal types of discourses under discussion involve imagery from maternal and familiar discourse, the “biological” discourse related to hygiene, the sexual discourse, the mock feminist discourse, the discourse of the military and the propaganda of the common good, and the discourse related to the animal world.